A co-creation roadmap towards sustainable quality of care: A multi-method study - Claessens, Fien; Seys, Deborah; Brouwers, Jonas; Van Wilder, Astrid; Jans, Anneke; Castro, Eva Marie; Bruyneel, Luk; De Ridder, Dirk; Vanhaecht, Kris (PLOS ONE, 2022)
Objective Hospitals demonstrated increased efforts into quality improvement over the past years. Their growing commitment to quality combined with a heterogeneity in perceptions among healthcare stakeholders cause concerns on the sustainable incorporation of quality into the daily workflow. Questions are raised on the drivers for a sustainable hospital quality policy. We aimed to identify drivers and incorporate them into a new, unique roadmap towards sustainable quality of care in hospitals. Design A multi-method design guided by an eight-phase approach to develop a conceptual framework consists of multiple, iterative phases of data collection, synthesis and validation. Starting with a narrative review followed by a qualitative in-depth analysis and including feedback of national and international healthcare stakeholders. Setting Hospitals. Results The narrative review included 59 relevant papers focusing on quality improvement and the sustainability of these improved quality results. By integrating, synthesising and resynthesizing concepts during thematic and content analysis, the narrative review evolved to an integrated, co-creation roadmap. The Flanders Quality Model (FlaQuM) is presented as a driver diagram that features six primary drivers for a sustainable quality policy: (1) Quality Design and Planning, (2) Quality Control, (3) Quality Improvement, (4) Quality Leadership, (5) Quality Culture and (6) Quality Context. Six primary drivers are described in 19 building blocks (secondary drivers) and 104 evidence-based action fields. Conclusions The framework suggests that a manageable number of drivers, building blocks and action fields may support the sustainable incorporation of quality into the daily workflow. Therefore, FlaQuM can serve as a useful roadmap for future sustainable quality policies in hospitals and for future empirical and theoretical work in sustainable quality management.